German(ic) in language contact Grammatical and sociolinguistic dynamics (Volume 5) - Zimmer, Christian (Language Science Press, 2021)
It is well-known that contact between speakers of different languages or varieties leads to dynamics in many respects. From a grammatical perspective, especially contact between closely related languages/varieties fosters contact-induced innovations. The evaluation of such innovations reveals speakers' attitudes and is in turn an important aspect of the sociolinguistic dynamics linked to language contact. In this volume, we assemble studies on such settings where typologically congruent languages are in contact, i.e. language contact within the Germanic branch of the Indo-European language family. Languages involved include Afrikaans, Danish, English, Frisian, (Low and High) German, and Yiddish. The main focus is on constellations where a variety of German is involved (which is why we use the term 'German(ic)' in this book).